Utilization Of Plant as A Drug for Diabetes Mellitus By The Community Of Beutong District, Nagan Raya Regency - Icha Putrimarlin; Hasanuddin Hasanuddin; Safrida Safrida; Wardiah Wardiah; Dewi Andayani (Biosaintifika: Journal of Biology & Biology Education, 2022)
Diabetes mellitus is one of the leading causes of death in the world. Indonesia is a country with the 7th largest population of Diabetes mellitus sufferers in the world in 2015. Many people use plants as diabetes mellitus drugs, in Indonesia More than 500 types of plants have been shown to have hypoglycemic activity because these plants contain compounds that are efficacious as anti-diabetic. This study was aimed to determine as many types of plants as possible that are used as medicinal plants for diabetes mellitus in Beutong sub-district, Nagan Raya district. This research was conducted by conducting interviews with 100 respondents aged 18-60 years who knew information about plants used for Diabetes mellitus.This study used the method of interview, observation, and identification (PlantNet). The results found as many as 29 species of plants from 26 families. Myrtaceae family as the most numerous plants with the number of species as much as 10% and the family Fabaceae with the number of species as much as 7%. Leaves are the part that is most widely used as medicine and the majority of people process it in a different way. Consume by drinking more than by chewing and the recommended dose for consumption is 2 times a day after meals. Benefits for researchers can add information about medicinal plants for diabetes mellitus utilized by the people of Beutong District, Nagan Raya Regency and become one of the references for public knowledge traditional, and become a reference material for students in conducting research next.